2020
DOI: 10.3390/biom10020237
|View full text |Cite
|
Sign up to set email alerts
|

Bioinformatics Analysis of Global Proteomic and Phosphoproteomic Data Sets Revealed Activation of NEK2 and AURKA in Cancers

Abstract: Tumor heterogeneity attributes substantial challenges in determining the treatment regimen. Along with the conventional treatment, such as chemotherapy and radiotherapy, targeted therapy has greater impact in cancer management. Owing to the recent advancements in proteomics, we aimed to mine and re-interrogate the Clinical Proteomic Tumor Analysis Consortium (CPTAC) data sets which contain deep scale, mass spectrometry (MS)-based proteomic and phosphoproteomic data sets conducted on human tumor samples. Quanti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
28
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 46 publications
2
28
0
Order By: Relevance
“…This technique has allowed to identify and dose-stratify the binding of the drug staurosphorine to 228 cellular kinases on a single experiment. Proteomic and phosphoproteomic analyses have also allowed to reveal mechanisms of activation of NEK2 and AURKA kinases in cancer ( 180 ), thus allowing the use of drugs targeting such kinases in six different cancer types within the Clinical Proteomic Tumor Analysis Consortium (CPTAC): Breast cancer, clear cell renal carcinoma, colon cancer, lung adenocarcinoma, ovarian cancer, and uterine corpus endometrial carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…This technique has allowed to identify and dose-stratify the binding of the drug staurosphorine to 228 cellular kinases on a single experiment. Proteomic and phosphoproteomic analyses have also allowed to reveal mechanisms of activation of NEK2 and AURKA kinases in cancer ( 180 ), thus allowing the use of drugs targeting such kinases in six different cancer types within the Clinical Proteomic Tumor Analysis Consortium (CPTAC): Breast cancer, clear cell renal carcinoma, colon cancer, lung adenocarcinoma, ovarian cancer, and uterine corpus endometrial carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…The phosphorylation of KRT19 has not been fully studied, and the phosphorylation of KRT19 in serine residues 35 plays a role in keratin filament assembly [68]; besides, the phosphorylation of KRT19 in the tyrosine residue 391 has been reported [69]. Although the importance of the possible phosphorylation of KRT19 in serine residues has not been sought, the phosphorylation in serine residue 14 has found hyperphosphorylated in breast, colon, ovarian cancer, lung adenocarcinoma, and uterine corpus endometrial carcinoma (UCEC) [70]. Our results identified the phosphorylation of KTR19 in serine residues; despite this, more extensive research is needed to determine the probable role that phosphorylated KRT19 plays in the progression of cervical cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Phosphorylation in serine residues of Cofilin 1 participates in its function regulation; phosphorylation of serine 3 inactivates this protein, and phosphoserine 24 may prevent the recognition of its nuclear localization signal [73]. This protein is upregulated in the presence of the enterovirus 71 in rhabdomyosarcoma [74], and the hyperphosphorylation of serine 7 was detected in various types of cancer [70], suggesting that Cofilin 1 has a role in cancer development. Interestingly, we found the phosphorylation of serine 7 in Cofilin 1 of CC.…”
Section: Discussionmentioning
confidence: 99%
“…Understanding the elementary molecular mechanisms of LUAD development to the identification of the therapeutic targets could considerably improve patient prognosis. Large expression profiling data sets have demonstrated to be beneficial in determining the regimen for cancer treatment (Deb et al 2020; Dong et al 2020; Klaeger et al 2017; Zhang et al 2020). In the post-genomic era, biological networks become a useful tool to understand gene regulation critically.…”
Section: Discussionmentioning
confidence: 99%
“…ASPM gene, which involved in mitotic spindle regulation, is responsible for the coordination of cell cycle. A recent study by Deb et al showed alteration of phosphorylation pattern in S425 position in ASPM targeted by Serine/threonine-protein kinase Nek2 (NEK2), is a common signature pattern for five cancer types including LUAD (Deb et al 2020). Wang et al assessed ASPM expression and the functional significance in LUAD and reported that increasing level of expression of ASPM was positively correlated with poor disease prognosis (Wang et al 2020).…”
Section: Discussionmentioning
confidence: 99%